New detrital zircon age and trace element evidence for 1450 Ma igneous zircon sources in East Antarctica - Paulsen, Timothy; Deering, Chad; Sliwinski, Jakub; id_orcid:0 000-0003-3069-9978; Bachmann, Olivier; Guillong, Marcel (Precambrian Research, 2017)
ISSN:0301-9268 ISSN:1872-7433